2020
DOI: 10.19109/ejpp.v7i1.5566
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation between Self-Regulation Learning and Listening Comprehension of the Eleventh Grade Students

Abstract: This research aimed to describe the correlation between self-regulation and listening comprehension. The method which was used in this research was correlational research. The population of the research was the eleventh grade students of SMA Muhammadyah 2 Palembang. There were 105 students from four classes as the population in this research. The sample was taken by using a total sampling which consists of 99 students. Furthermore, there were two variables in this research. The first one was self-regulation (v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Thus, they tried to choose a learning style that matched their conditions. Another study conducted by Puspita (2016), who investigated 254 Indonesian secondary-level students using correlational explanatory research design, also revealed that the six reading strategies strongly correlate with the student's reading comprehension. Yet, social and affective strategies only contributed inconsiderably to the student's reading comprehension.…”
Section: Previous Studiesmentioning
confidence: 89%
“…Thus, they tried to choose a learning style that matched their conditions. Another study conducted by Puspita (2016), who investigated 254 Indonesian secondary-level students using correlational explanatory research design, also revealed that the six reading strategies strongly correlate with the student's reading comprehension. Yet, social and affective strategies only contributed inconsiderably to the student's reading comprehension.…”
Section: Previous Studiesmentioning
confidence: 89%
“…A complete and entire understanding is required to understand what is being said (Azizah ,2014). It signifies that understanding is knowing what someone is saying, and comprehending what someone is saying requires talent to be able to fully understand what has been said by the speakers (Lestari, 2017).…”
Section: Listening Comprehension and Reading Comprehension 231 Concep...mentioning
confidence: 99%
“…It means that there are two groups of students, namely experimental group and control group. The experimental group is taught by using English songs while control the group is taught without using English songs (Lestari, 2017). The population of this research is very important.…”
Section: Introductionmentioning
confidence: 99%